Analisis Strategi Peningkatan Penjualan Toko Online Danangshoop Dengan Metode Market Basket Analysis - Setiadji, Bayu Rizqi; Hidayat, Rahmat; Faishal Rizki Nandasati; Nafira Eldita Cahya; Shofa, Mohamad Jihan (Fakultas Teknik Universitas Tulang Bawang, 2024)
Danangshoop is an online store that focuses on agriculture and sells plant seeds. On its journey, Danangshoop encountered a problem in its e-commerce system, specifically the unsequential arrangement of products in the best-selling column. This research are meant to change the sequence of best-selling products in order according to the total number of purchases per product. Market Basket Analysis is the method used to analyze consumer purchasing patterns, and the results are the basis for marketing strategies that enhance sales targets. The implementation of Market Basket Analysis helps in designing promotions and product placements intelligently. This research uses a quantitative approach, analyzing data by calculating confidence and support values. The lift analysis results indicate that a combination of vegetable seeds and fruit seedlings has the most significant impact on the purchase of vegetable seeds. The conclusion highlights a variety of products, especially vegetable seeds that are in demand among consumers. The store can enhance promotions by featuring vegetable seed products in the